Childhood vaccination views across genders: what do mothers and fathers really think? - Manas, Nur Hidayahtul Nabihah; Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Osman, Muhammad Redzuan; M. Pd, Muhammad Iqbal (Faculty of Administrative Science and Policy Studies, 2025)
Childhood vaccination is a crucial public health endeavour aimed at preventing infectious illnesses and decreasing child mortality. Although vaccine uptake in Malaysia is generally high, disparities may occur among different demographic groups, including gender. This study evaluates parental views regarding childhood vaccination in Pahang, Malaysia, and assesses whether these attitudes significantly differ between male and female parents. The target population comprised parents who have at least one child under 15 years of age. A quantitative cross-sectional design was utilised, involving 333 parents from Pahang. Data were gathered via a structured questionnaire assessing views regarding childhood vaccination. Descriptive statistics and an independent samples t-test were performed to assess attitudes and gender differences, respectively. The independent t-test revealed a statistically significant disparity between male and female parents, with female parents exhibiting more favourable attitudes toward childhood vaccination. The findings highlight the significance of gender in influencing parental perspectives on immunisation. This study advances the application of Gender Schema Theory in public health research and highlights the need for gender-sensitive strategies to improve vaccine acceptance, particularly among male parents.